2013
DOI: 10.5539/jfr.v2n3p110
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Lightly Salted Atlantic Salmon Fillets Injected With Brine Solutions Containing Sodium Bicarbonate

Abstract: The objective of this study was to produce lightly salted Atlantic salmon (Salmo salar L.) fillets with improved technical and sensory attributes. Brine containing 0, 50, 150 or 250 g/L NaCl with or without additional 25 g/L sodium bicarbonate (NaHCO 3 ) was injected into the fillets. 24 hours after injection, the muscle NaCl concentration ranged from 0.2 to 2.4%, and pH ranged from 6.18 to 6.48. Untreated fillets lost 1% weight, whereas the weight increase was 4% of the fillets injected with NaCl or a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Brines with added NaHCO 3 have been shown to cause flesh darkening and improved texture, aroma and shelf life of fish fillets . The flesh of gadoids should preferably have a light and glossy appearance, so darkening associated with elevated muscle pH and protein denaturation leading to a changed pattern of light reflection is not desirable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Brines with added NaHCO 3 have been shown to cause flesh darkening and improved texture, aroma and shelf life of fish fillets . The flesh of gadoids should preferably have a light and glossy appearance, so darkening associated with elevated muscle pH and protein denaturation leading to a changed pattern of light reflection is not desirable.…”
Section: Discussionmentioning
confidence: 99%
“…solubility and water binding) are important during and after processing, as they influence the proteins' ability to interact with other components and thus affect the overall product quality . Salting with a combination of NaCl and sodium bicarbonate (NaHCO 3 ) has shown improved yield and liquid retention in fish and other meat products, coinciding with enhanced texture, flavor and odor, reduced development of unpleasant volatile organic compounds and darker flesh color . Recently it was also shown that the effects of NaHCO 3 are dependent on the concentration of NaCl …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of fish was added in excess salt to extend shelf life but were not effectively dried to maintain quality after pickling, leading to sharply decrease on the safety of products and potential harm to consumers' health [1]. And lower salt content was proved to be effective on the stability of storage and sensory attributes [2].…”
Section: Introductionmentioning
confidence: 99%